Clinical and immunological characteristics of moderate-to-severe forms of COVID-19 at different levels of the tissue damage marker (lactate dehydrogenase) - I. P. Sizyakinа; V. Ya. Zakurskayа; N. A. Skripkinа; E. A. Antonova; D. B. Sizyakin (Медицинский вестник Юга России, 2021)
Objective: To study the features of the immune status in patients with a moderate-to-severe course of COVID-19, depending the levels of blood lactate dehydrogenase.Materials and Methods: A total of 24 patients with a moderate-to-severe form of COVID-19 were examined. The control group consisted of 21 healthy volunteers. Methods: clinical, paraclinical (computed tomography of the lungs; complete blood count, blood biochemistry; immunological studies), statistical.Results: Changes in complete blood count and blood biochemistry in patients with moderate-to-severe COVID-19 consist in granulocytosis, lymphopenia, monocytopenia, and an increase in the level of C-reactive protein, lactate dehydrogenase, with a simultaneous decrease in the total protein content. In patients with high levels of lactate dehydrogenase, a redistribution of lymphocyte populations towards B-cells was revealed with a decrease in the total number of T-cells. At the same time, there was a decrease in the production of IgM and IgG and a simultaneous increase in the synthesis of IgA.Conclusions: The increase in blood LDH in COVID-19 patients is associated with a decrease in the content of T-cells due to severe lymphopenia, and a simultaneous increase in the content of B-cells without adequate enhancement of their antibody production function.